2014
DOI: 10.1039/c4cp00103f
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of a model porphyrin within poly(ethylene glycol) (PEG): effect of water, PEG molecular weight, ionic liquids, salts, and temperature

Abstract: Understanding molecular aggregation within environmentally-benign media is of utmost importance. Aggregation of a common porphyrin, 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin (TSPP), dissolved in media composed of poly(ethylene glycols) (PEGs) up to an average molecular weight (MW) of 8000 as major components, is investigated. J-aggregates of TSPP are well-manifested via the bathochromically-shifted UV-vis absorbance band of TSPP. As media, 10 wt% water-added PEGs at pH 1 show excellent efficiency for TSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…TriPEG‐galloyl pheophorbide and triPEG‐chlorin (entries 2 and 4) led to a lipophilic deamplification by 1.9 log units compared to unsubstituted sensitizers, respectively (entries 1 and 3). Lower log P values of PEGylated compounds would be expected, where their curling onto the porphyrin ring inhibits aggregation due to π–π stacking forces . The reduced log P of the PEGylated pheophorbide versus native hydrophobic pheophorbide‐ a will make the former more accessible and less prone to aggregating, to potentially address the challenge in sterilization of surgical margins.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…TriPEG‐galloyl pheophorbide and triPEG‐chlorin (entries 2 and 4) led to a lipophilic deamplification by 1.9 log units compared to unsubstituted sensitizers, respectively (entries 1 and 3). Lower log P values of PEGylated compounds would be expected, where their curling onto the porphyrin ring inhibits aggregation due to π–π stacking forces . The reduced log P of the PEGylated pheophorbide versus native hydrophobic pheophorbide‐ a will make the former more accessible and less prone to aggregating, to potentially address the challenge in sterilization of surgical margins.…”
Section: Resultssupporting
confidence: 86%
“…Lower log P values of PEGylated compounds would be expected, where A. A. Ghogare and A. Greer: Synthesis of a poly(ethylene glycol) galloyl sensitizer tip their curling onto the porphyrin ring inhibits aggregation due to π-π stacking forces [60][61][62][63][64][65][66]. The reduced log P of the PEGylated pheophorbide versus native hydrophobic pheophorbide-a will make the former more accessible and less prone to aggregating, to potentially address the challenge in sterilization of surgical margins.…”
Section: Sensitizer Design and Solubility (Table 1)mentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36] Suggestion that solvated electrons in ionic liquids produce absorption spectra is corroborated by a report where it is found that the solvated electron exhibits an absorption spectrum peaking in the 1000-1400 nm region and a second absorption band peaking in the UV region. [26][27][28][29][30][31][32][33][34][35][36] Suggestion that solvated electrons in ionic liquids produce absorption spectra is corroborated by a report where it is found that the solvated electron exhibits an absorption spectrum peaking in the 1000-1400 nm region and a second absorption band peaking in the UV region.…”
Section: Uv/vis Absorbance Spectroscopymentioning
confidence: 91%
“…29 , respectively, to TSPP dissolved in 10 wt% water added PEGs at pH 1 results in increased J-aggregation efficiency. 29 , respectively, to TSPP dissolved in 10 wt% water added PEGs at pH 1 results in increased J-aggregation efficiency.…”
Section: Uv/vis Absorbance Spectroscopymentioning
confidence: 99%
“…Biswas et al [18] explained polymer template enhanced J-aggregation of porphyrin dyes by ionic interactions of the cationic side chains of the functionalized polymer under acidic conditions with the negatively charged sulfonate groups of the porphyrins. Rai et al [19] have found that poly(ethylene glycol) chain length and electrostatic interactions play a major role in porphyrin J-aggregation efficiency.…”
Section: Introductionmentioning
confidence: 99%